The dilemma - Howard, Ron, 1954-; Grazer, Brian, 1953-; Loeb, Allan; Vaughn, Vince; James, Kevin, 1965-; Connelly, Jennifer; Ryder, Winona, 1971-; Tatum, Channing; Morton, Amy.; Latifah, Queen; Universal Pictures (Firm); Imagine Entertainment (Firm); et al. (Universal City, CA : Universal Studios Home Entertainment, 2011)
Ronny's world is turned upside down when he inadvertently sees something he should not have and makes it his mission to get answers. As the amateur investigation dissolves his world into comic mayhem, he learns that his best friend Nick has a few secrets of his own. Now, Ronny must decide what will happen if he reveals the truth.
DVD, NTSC, region 1, anamorphic widescreen (2.35:1), dual layer, Dolby digital 5.1 surround, Dolby digital 2.0 stereo.
English, French or Spanish dialogue; French or Spanish subtitles. Subtitled for the deaf and hard of hearing; audio described for the visually impaired.
Vince Vaughn, Kevin James, Jennifer Connelly, Winona Ryder, Channing Tatum, Amy Morton, Queen Latifah.
Director of photography, Salvatore Totino ; editors, Mike Hill and Dan Hanley ; music, Hans Zimmer and Lorne Balfe.
MPAA rating: PG-13; for mature thematic elements involving sexual content.
Bonus features: alternate ending; deleted scenes with commentary by director Ron Howard; gag reel.
Keywords: Male friendship -- Drama; Adultery -- Drama; Amistad -- Teatro; Adulterio -- Teatro; Feature films; Comedy films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Comedy films; Comedy